2005
DOI: 10.1128/jcm.43.4.1902-1909.2005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Hepatitis C Virus Genotype 4 Isolates in Egypt and Analysis of the Variability of Envelope Proteins E1 and E2 in Patients with Chronic Hepatitis

Abstract: We analyzed hepatitis C virus (HCV) genotype 4 isolates circulating in the Alexandria District (Egypt) in terms of genetic divergence and the presence of different subtypes. Hypervariable region 1 (HVR1) and the NH2 region of the E2 protein were characterized, and the heterogeneity of subtype 4a isolates was evaluated by analyzing epitope frequencies, immunoproteasome prediction, and possible glycosylation patterns. The heterogeneity of the nucleotide sequences was greater than that found in previous studies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 56 publications
6
28
2
Order By: Relevance
“…In this study, it was found that the prevalent HCV genotype was type 4a, this is in accordance with the finding that genotype 4 (HCV-4) is the most common variant of the hepatitis C virus (HCV) in the Middle East and Africa, particularly Egypt [27,28].…”
Section: Histopathological Featuressupporting
confidence: 76%
“…In this study, it was found that the prevalent HCV genotype was type 4a, this is in accordance with the finding that genotype 4 (HCV-4) is the most common variant of the hepatitis C virus (HCV) in the Middle East and Africa, particularly Egypt [27,28].…”
Section: Histopathological Featuressupporting
confidence: 76%
“…In fact, the HCV genotype 4 was detected in 65 out of 70 patients (92.86%), supporting earlier studies (14,(31)(32)(33)(34)(35)(36). However, our data also show that the contribution of genotype 4 to the study pool is not exclusive and that other genetically related genotypes exist in the population, confirming previous studies (14,37,38). One cansuggest a deficiency of the multiplex PCR in subtyping genotype 4, but inclusion of more primers would be an unjustified burden on an already financially challenged health care system, in the absence of sufficient evidence to support clinical and therapeutic outcomes (23,24).…”
Section: Discussionsupporting
confidence: 92%
“…HCV genotype 4 represents more than 17 million total global HCV infections and is prevalent in Africa, the Middle East, and some European countries [29,30]. The analysis of HCV genotype 4 in Egypt demonstrated that HCV genotype 4a is extremely variable from other genotypes in terms of sequences and immunological determinants that might alter virus-host interaction and cytokine production [31]. On the other hand, IL-4 is mainly produced by activated Th2 cells that also produce IL-5 and IL-13.…”
Section: Discussionmentioning
confidence: 99%